Pro Environmental Behavior in Islamic Boarding Schools: A Systematic Literature Review on Religiosity, Ecological Awareness, and Social Norms - Purnama Aksir, Rahmad; Abd. Madjid; Azam Syukur Rahmatullah; Fitriah M. Suud; Sittie Noffaisah Pasandalan (ANFUSINA: Journal of Psychology, 2025)
The global environmental crisis has led to increasing academic attention toward factors that influence pro-environmental behavior, including within religious education contexts such as Islamic boarding schools (pesantren). This study aims to conduct a Systematic Literature Review (SLR) of empirical research examining the influence of religiosity and ecological awareness on pro-environmental behavior, as well as the role of social norms as a reinforcing factor within Islamic boarding school (pesantren) communities. The SLR process followed the PRISMA framework, including the stages of identification, screening, eligibility assessment, and final inclusion of articles. Literature was collected from the Scopus and Web of Science databases using inclusion criteria that required publications to be internationally recognized, published between 2015 and 2025, relevant to the themes of religiosity, ecological awareness, pro-environmental behavior, and social norms, and employing empirical research designs. The selected articles were analyzed thematically and conceptually to identify patterns of findings, consistency of results, and existing research gaps. Complementing the SLR, this study also employed bibliometric analysis using VOSviewer to map the intellectual structure, thematic clusters, and global research trends related to the topic. The SLR results indicate that religiosity functions as a moral foundation that strengthens individuals’ internal norms to protect the environment, while ecological awareness enhances cognitive understanding and readiness to engage in pro-environmental actions. Social norms, particularly within Islamic boarding school (pesantren) communities characterized by communal and hierarchical social structures, were found to reinforce the relationship between religiosity, ecological awareness, and pro-environmental behavior. The bibliometric analysis further revealed three dominant domains in the global literature: ecological consumption behavior, environmental crises, and reflective ecocritical narratives, which enrich the conceptual understanding of the SLR findings. Overall, this study highlights that the pro-environmental behavior of santri emerges from the interaction between religious values, ecological literacy, and institutional social norms. These findings provide both theoretical and practical implications for the development of more systematic, evidence-based, and sustainable eco-pesantren programs. Keywords : Religiosity, Ecological Awareness, Pro-Environmental Behavior, Social Norms, Islamic Boarding Schools.